A case of ustekinumab-induced pustular psoriasis was treated with IL-17A inhibitor - LIN Junjie; OU Min; LI Yang; SHE Xinyan; CAI Liting; GUAN Zepu; WANG Xiaohua (Pifu-xingbing zhenliaoxue zazhi)
We report a case of ustekinumab-induced pustular psoriasis treated with IL-17A inhibitor. A 51-year-old female presented with red plaques and scales for 20 years, with aggravation and pustules for over 10 days. The patient was previously diagnosed with plaque psoriasis, and poorly responded to systemic medications. After ruling out contraindications, the patient was subcutaneously given 45 mg of ustekinumab, resulting in clearance of the skin lesion. But erythema and scales with pustules appeared all over the body after the fourth treatment. Physical examination revealed scattered red plaques covered with white-silver scales, and Auspitz sign (+) on the head and face. The trunk and limbs were scattered with large erythematous patches and erythematous plaques, covered with various size of dense pustules, in a target-shape with a brown center. Some pustules merged to pus-lake. Pustules with erosive surface were scattered on the vulvar mucosa. Nails appeared thimble-like with nail plate thickening. Histopathology showed hyperkeratosis, parakeratosis, thinning or disappearance of granular layer, psoriasis-like epidermal hyperplasia, Munro and Kogoj microabscesses, papillary dermal edema, vascular dilation, and perivascular lymphocytic infiltration. Diagnosis was pustular psoriasis. After the treatment with topical corticosteroids and 160 mg of ixekizumab, the rashes subsided within 3 days. Afterwards, patient was treated with ixekizumab according to the manufacturer′s instruction, without the development of new lesion during 1-year follow-up.